Testosterone Treatment of Pubertal Delay in Duchenne Muscular Dystrophy - Wood, Claire L.; Cheetham, Tim D.; Guglieri, Michela; Bushby, Kate; Owen, Catherine; Johnstone, Helen; Straub, Volker (Neuropediatrics, 2015)
Background The outlook for adolescents with Duchenne muscular dystrophy (DMD) has improved greatly as a result of corticosteroid use, but treatment will compromise growth and delay puberty. Whether exogenous testosterone can promote growth, development, and skeletal health is unclear.Methods We collected data retrospectively on growth and pubertal response in 14 adolescents with DMD who were treated with testosterone between 2008 and 2014.Results A total of 14 boys were treated at a median age of 14.5 years. Eight have finished treatment after a mean age of 3.1 years and the feedback from families was generally positive. The mean testicular volume pretreatment was 2.4 and 3.9 mL posttreatment. The mean baseline testosterone concentrations were < 1.0 and 5.4 nmol/L postintervention. Median height velocity increased from 0.45 cm/y before treatment to 3.6 cm/y after the treatment. The mean height gain was 14.2 cm.Conclusions A broad range of testosterone preparations was used. Testosterone was generally well-liked, but side effects were experienced by some patients and the pubertal growth increment appears to be compromised. Few subjects had adult endogenous testosterone levels posttreatment. Controlled studies are required to determine the most appropriate treatment regimen and the precise impact of testosterone on key outcomes, such as muscle function and bone integrity. Clinicians will then be better placed to advise families about likely benefits and risks.
Keywords: Duchenne muscular dystrophy; growth; puberty; hypogonadism; corticosteroids; testosterone